Viral Hemorrhagic Septicemia - Iowa State University Center for Food Security and Public Health (Iowa State University Digital Repository, 2007)
Viral hemorrhagic septicemia (VHS) is a serious systemic disease of fish. The VHS virus (VHSV) is carried by at least 50 species of marine and freshwater fish. The infection is subclinical in some species, but it is associated with severe disease and high mortality rates in others. Clinical infections are economically important in farmed fish, particularly rainbow trout, turbot and Japanese flounder. Outbreaks have also been reported in some wild populations, including Pacific herring and pilchard along the Pacific coast of North America. Recently, viral hemorrhagic septicemia has become an emerging disease of freshwater fish in the Great Lakes region of North America. The virus was apparently introduced into this region by 2003, and deaths have been reported since 2005. Massive die-offs have occurred in some wild species. Affected fish include several warm-water species previously thought to be resistant to VHS. The epizootic seems to be caused by a new substrain of VHSV. The source of this virus is unknown, but it may be a mutated marine virus that became pathogenic for naïve freshwater fish. This isolate causes moderate mortality in salmonid species not affected by other VHSV isolates, including Pacific (chinook) salmon, and could threaten farmed salmonids in the area.